Intracellular pathogen effector reprograms host gene expression by inhibiting mRNA decay - Yevgen Levdansky; Justin C. Deme; David J. Turner; Claire T. Piczak; Filip Pekovic; Anna L. Valkov; Sergey G. Tarasov; Susan M. Lea; Eugene Valkov (Nature Communications)
Abstract Legionella pneumophila, an intracellular bacterial pathogen, injects effector proteins into host cells to manipulate cellular processes and promote its survival and proliferation. Here, we reveal a unique mechanism by which the Legionella effector PieF perturbs host mRNA decay by targeting the human CCR4–NOT deadenylase complex. High-resolution cryo-electron microscopy structures and biochemical analyses reveal that PieF binds with nanomolar affinity to the NOT7 and NOT8 catalytic subunits of CCR4–NOT, obstructing RNA access and displacing a catalytic Mg²⁺ ion from the active site. Additionally, PieF prevents NOT7/8 from associating with their partner deadenylases NOT6/6L, inhibiting the assembly of a functional deadenylase complex. Consequently, PieF robustly blocks mRNA poly(A) tail shortening and degradation with striking potency and selectivity for NOT7/8. This inhibition of deadenylation by PieF impedes cell cycle progression in human cells, revealing a novel bacterial strategy to modulate host gene expression.